Changes to Intermediary Metabolites in Sporadic and LRRK2 Parkinson's Disease Demonstrated by Proton Magnetic Resonance Spectroscopy. (18th August 2015) - Aasly, Jan O.; Sæther, Oddbjørn; Johansen, Krisztina K.; Bathen, Tone F.; Giskeødegård, Guro F.; White, Linda R.
Abstract : Background . Parkinson's disease (PD) remains a clinical diagnosis and biomarkers are needed to detect the disease as early as possible. Genetically determined PD provides an opportunity for studying metabolic differences in connection with disease development. Objectives . To study the levels of intermediary metabolites in cerebrospinal fluid (CSF) from patients with PD, either of sporadic type or in carriers of the LRRK2 p.G2019S mutation. Methods . Results from patients with sporadic PD or LRRK2 -PD were compared with asymptomatic LRRK2 mutation carriers and healthy control individuals. CSF was analysed by proton MR spectroscopy ( 1 H-MRS) giving reliable results for 16 intermediary metabolites. Partial least squares discriminant analysis (PLS-DA) was applied to study group differences. Results . PLS-DA distinguished PD patients from healthy individuals based on the metabolites identified in CSF, with 2-hydroxybutyrate, glutamine, and dimethyl sulphone largely contributing to the separations. Conclusion . Speculatively, all three metabolites could alter concentration in response to metabolic changes connected with neurodegeneration; glutamine as a means of removing excess nitrogen from brain, dimethyl sulphone as an anti-inflammatory agent, and 2-hydroxybutyrate in connection with altered glutathione metabolism. Potentially, 1 H-MRS is a promising tool for identifying novel biomarkers for PD.